Perception of Nursing Students towards their Profession in Morang District - Paudel, Diksha; Bhandari, Bhawana; Khatiwada, Sarita; Gurung, Sunita (Journal of Advanced Academic Research, 2023)
Background:Nursing is indeed considered a noble and essential profession in society because of the core value it promotes in its practice-which is the care of life. Nursing student’s perception towards the image of the nursing profession has an apparent impact on their self-concept, self-esteem, recruitment, retention, and performance. Thus, nurses who have positive professional images have good knowledge retention. Methodology: A descriptive cross-sectional study were conducted among nursing students in Purbanchal University School of Health Sciences through self-administration question. Data collection involved assessment of nursing student’s perception towards their profession through census method. Chi-square was done to examine associations between perception of profession and its factors. Results: The 126 participants were included in this study; most of them 60.8% were studying in 1st year. This study mentioned that 51.6%had positive perception and found a significant relationship between perception and the age of the respondents. This suggests that the way respondents perceive the profession is influenced by their age.